Non-fixation versus fixation of mesh in laparoscopic transabdominal preperitoneal repair of inguinal hernia: A systematic review and meta-analysis of randomized controlled trials - Zhang, ChenXin; Li, Jia; Suo, HaiJin; Bai, JianPing (PloS one, 2024)
The impact of non-fixation of mesh in transabdominal preperitoneal (TAPP) inguinal hernia repair has not been fully assessed. The aim of this meta-analysis was to comprehensively compare the clinical outcomes of non-fixation and fixation of mesh in TAPP to determine whether non-fixation could affect the outcomes. PubMed, Embase and CENTRAL were searched for studies on TAPP repair of inguinal hernia and mesh fixation published up to June 2023. The literature search was completed on June 22, 2023. Randomized controlled trials that compared perioperative outcomes between mesh fixation and non-fixation without using self-gripping mesh were included. The primary outcome measures were recurrence and evaluation of postoperative pain, while secondary outcome measures included time to normal activity, infection rate and formation of seroma. Subgroup analyses and sensitivity analysis were also conducted. Six randomized controlled trials were included, involving 679 patients who underwent TAPP with non-fixation and 964 patients with fixation of mesh. There was no significant difference in recurrence between the two groups (RR: 0.83; 95% CI, 0.29-2.39, P = 0.73). The non-fixation group had less pain than the fixation group at 6 months postoperatively (MD: -0.16; 95% CI, -0.23--0.10, P < 0.0001). Additionally, there was no significant difference in the time to return to normal activity or rates of infection or seroma formation between the two groups (MD: -4.95; 95% CI, -11.36-1.45, P = 0.13; RR: 1.18; 95% CI, 0.39-3.62, P = 0.77; RR: 0.94; 95% CI, 0.63-1.40, P = 0.75). Based on the current evidence, non-fixation without using self-gripping mesh may not affect the efficacy of TAPP. It does not increase recurrence rate and may result in less postoperative pain in inguinal hernia with small hernia defect (less than 3cm).